Implementasi Teknologi QR Code Pada Pengarsipan Bukti Pembayaran di kampus IIB Darmajaya - Purdadi, Iqbal Gymnastiar; Al Anshori, Fauzan Ahmad; Alfitrah, Muhammad Dafa (Journal of Digital Literacy and Volunteering, 2023)
The QR code is a two-dimensional barcode matrix code created by a Japanese company, DensoWave in 1994. "QR" which stands for "Quick Response" can contain many kinds of information in it such as text, URL addresses, telephone numbers, and other files. QR codes are usually applied to various products or goods to show additional information about the product or item. To find out what is in the QR code, you need a smartphone with a camera that can scan the QR code. The rapid development of the times and the increasingly creative mindset of humans have resulted in many thoughts. Many people are starting to compete to be able to lighten the job and make work more effective. This creates various ways or methods that make life easier. Not only work hard but also work smart. Implementation of various methods and combining one method with other methods is starting to be widely applied. For example in this study where this research discusses implementing the use of QR codes for archiving proof of payment.